Implementasi Perangkat Pembelajaran Bahasa Inggris Bisnis - Dini Riandini; Faridatun Nida (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Emergence of Business English as a part of English for Specific Purpose gives another challenge to lecturers in providing learning tools that is accordance to the learning objectives. This phenomenon becomes the basis to the aim of the research, that is to know the implementation of Business English module as a learning tool and to examine its eligibility through the lecturer’s ability and students’ response in using that tool. By involving 4D model, the result of analysis can answer the research aim. Literature review to several Business English lesson plan and need analysis to student university related to the Business English learning makes the arranged material relevant and relate to the students need, especially for facing the business and work activities. Lecturers ability to use the module and the practical knowledge of the use of English in business supports the eligibility of the module as a learning tool of Business English course. Meanwhile, students response is also good because they thought that the material is considerably applicable to their activities. The elegibility among the material, lecturer’s ability and students response leads to a conclusion that Business English module is eligible to be implemented in Business English course.